Spatial Autocorrelation Unemployment and Poverty in the Eastern Part of Indonesia - Lizarifah, Lizarifah; Yulianita, Anna; Bashir, Abdul (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
This study aims to analyze the spatial interaction of unemployment and poverty in general and locally and identify patterns and structures of economic growth on the islands of Sulawesi and Papua for the 2016-2020 period. The research method used is Moran Scatterplot, Local Indicator of Spatial Autocorrelation (LISA) and Klassen Typology. Moran's Test showed on the poverty variable has a positive spatial autocorrelation and the unemployment variable has a negative spatial autocorrelation. The results of the LISA test mapped the poverty variable in 2016 into L-L criteria in Central Sulawesi Province and in 2020 in Central Sulawesi and South Sulawesi Provinces. Meanwhile the unemployment variable in 2016 maps Papua Province into L-L criteria, in 2020 Southeast Sulawesi Province is classified as H-H criteria and Papua Province is classified as L-H criteria. Klassen's analysis classifies two provinces in Quadrant I, five provinces in Quadrant III and one province in Quadrant IV.